Cedar Rapids [ - Arteta, Miguel; Heche, Anne; Helms, Ed; Reilly, John C. (Fox Searchlight Pictures, 2011)
For 18 + with elements for mature audiences (violence, horror, sex, politics, religion, counter-culture) (18)